Effects of large spanwise wavelength on the wake of a sinusoidal wavy cylinder. (February 2016) - Lin, Y.F.; Bai, H.L.; Alam, Md. Mahbub; Zhang, W.G.; Lam, K.
Abstract: The wake of a sinusoidal wavy cylinder with a large spanwise wavelength λ / D m (=3.79–7.57) and a constant wave amplitude a / D m =0.152, where D m is the mean diameter of the cylinder, is investigated using three dimensional (3D) large eddy simulation (LES) at a subcritical Reynolds number Re =3×10 3, based on incoming free-stream velocity ( U ∞ ) and D m . Attention is paid to assimilating the effects of λ / D m on the cylinder wake, including vortex shedding frequency, spanwise vortex formation length, streamwise velocity distribution, flow separation angle, 3D vortex structure, and turbulent kinetic energy (TKE) distribution. Based on the predominant role of λ / D m in the near wake modification, three regimes are identified, i.e., regime I at λ / D m <6.0, regime II at λ / D m ≈6.0 and regime III at λ / D m >6.0. A dramatic decrease in fluid forces is observed at λ / D m =6.06, about 16% and 93% reduction in time-averaged drag and fluctuating lift, respectively, compared to those of a smooth cylinder. We identified, for the first time, an optimum λ / D m (=6.06) for the wavy cylinder with relatively large λ / D m (>3.5) in the subcritical flow regime. The underlying mechanisms of force reduction are discussed, including the flow characteristics at the three λ / D m regimes. A comparison is also made between the results of λ / D m effects on the near wakes of a circular and a square cylinder.